2017
DOI: 10.1088/1741-4326/aa700b
|View full text |Cite
|
Sign up to set email alerts
|

Role of a continuous MHD dynamo in the formation of 3D equilibria in fusion plasmas

Abstract: Stationary 3D equilibria can form in fusion plasmas via saturation of magnetohydrodynamic (MHD) instabilities or stimulated by external 3D fields. In these cases the current profile is anomalously broad due to magnetic flux pumping produced by the MHD modes. Flux pumping plays an important role in hybrid tokamak plasmas, maintaining the minimum safety factor above unity and thus removing sawteeth. It also enables steady-state hybrid operation, by redistributing non-inductive current driven near the center by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 47 publications
8
28
0
Order By: Relevance
“…Experiments performed in RFX-mod tokamak plasmas confirmed the predictions [20]. These results have been proved to be relevant also for high- DIII-D plasmas when a helical core forms induced by an external n=1 MP and can explain the observed central current redistribution [21] Experiments have been performed to investigate the role of the ion mass M i on plasma dynamics in the RFP. Interestingly, the existing main magnetic configurations are characterized by largely different responses to the change of the working gas.…”
Section: Internal Transport Barriers and Helical State Formationsupporting
confidence: 68%
“…Experiments performed in RFX-mod tokamak plasmas confirmed the predictions [20]. These results have been proved to be relevant also for high- DIII-D plasmas when a helical core forms induced by an external n=1 MP and can explain the observed central current redistribution [21] Experiments have been performed to investigate the role of the ion mass M i on plasma dynamics in the RFP. Interestingly, the existing main magnetic configurations are characterized by largely different responses to the change of the working gas.…”
Section: Internal Transport Barriers and Helical State Formationsupporting
confidence: 68%
“…In many tokamaks such as DIII-D, it was reported the sawtooth-free hybrid plasma was realized by "flux pumping" with HCs [6,7]. In this study, the sawtooth-free phase is also observed with an m/n = 2/1 NTM as seen in figure 3.…”
Section: Discussionsupporting
confidence: 57%
“…Helical cores (HCs) in tokamaks have been an important research topic for the fusion reactor because HCs can affect transports of impurities [1][2][3][4], energetic particles [5], or toroidal momentum [5]. In addition to the effect on transport by helical structures, recent studies suggested that magnetohydrodynamics (MHD) dynamo accompanied with HCs redistributes the current profile in the core and realizes sawtooth-free plasmas of hybrid scenarios as observed in DIII-D [6,7], in which the minimum value of the safety factor profile, qmin., is kept slightly above unity by "flux pumping".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact in the absence of this term a purely helically deformed plasma could hardly satisfy the constraint imposed by the single fluid electron momentum balance [9]. A dynamo electric field generated by a single dominant mode has been estimated recently in [19], where the radial profile of the dynamo electric potential, as deduced by equilibrium reconstructions, was estimated (see figure 8 of [19]), with a very similar shape to the case with 40% dissipation (and with Δ=0) shown in figure 2(b) of this paper. In [20,21] it was assumed that the α-dynamo contributed to the transport of total helicity from the fluctuations to the macroscale.…”
Section: Discussionmentioning
confidence: 99%